Crime victims and the right to compensation: International standards and challenges in Serbia - Kolaković-Bojović Milica (Crimen (Beograd), 2025)
In this paper author sheds a light to the right to compensation for crime victims in Serbia, analyzing it from the multiple perspective: the relevant international standards, applicable national legal framework, the current state of play in the practice of Serbian courts, the recent progress made, as well as in term of the remaining challenges. The analysis shows that even though the national legal framework on compensation for crime victims provides for the solid ground for exercising this right, the reality seems to be quite different. Discouraged by the practice of regular referral to the civil proceedings, paired with a lack of legal aid in the process of claiming compensation or even discouraged by lawyers who represent them, victims are not skilled, empowered and/or supported enough to submit a compensation claim in criminal proceeding and pass through this process saved by a various protective measures that belongs to victims in criminal proceedings and especially those that are especially vulnerable. Neither legal nor institutional set up allows for compensation from a state fund in cases when there is no possibility for a victim to be compensated from an offender from various reasons (offender unknown or died or has no resources/property).